Progression in immunotherapy for advanced prostate cancer - Liang, Hao; Liu, Yang; Guo, Jiao; Dou, Maoyang; Zhang, Xiaoyi; Hu, Liyong; Chen, Jun (Frontiers in Oncology, 2023)
Prostate cancer (PCa) is one of the most common malignant cancers of the male genitourinary system, with a high morbidity and mortality rate. Currently, treatment modalities for localized prostate cancer mainly focus on radical prostatectomy or radical radiotherapy. However, some patients still experienced disease recurrence or progression after the treatment above; some were already at an advanced stage or have metastasis at the diagnosis time. With the continuous development and progress of medicine in recent years, immunotherapy has become a revolutionary way of cancer treatment, which has gained remarkable accomplishment in treating hematologic malignancies. A variety of immunotherapy has also appeared in the field of advanced prostate cancer treatment, including therapeutic vaccines and immune checkpoint therapies. Several immunotherapy modalities have shown initial success. Despite the milestones in the immunotherapy of prostate cancer, its application in the clinical setting is still limited. Though being an optional treatment for prostate cancer, immunotherapy needs to be explored by more extensive and in-depth studies in the future.